Comparison of the Transduction Capacity of AAV5 and AAV PHP.eB Serotypes in Hippocampus Astroglia - Anastasia Borodinova; Victor Ierusalimsky; Pavel Balaban (Neuroglia, 2023)
In the present study, we compared the astrocyte-transducing potential of the relatively novel engineered AAV PHP.eB serotype and the well-examined conventional AAV5 serotype. We generated the AAV-based genetic constructs with membrane-bound fluorescent markers under the control of the astroglial promoter GfaABC1D to target astrocytes in vivo, either via local injection into the hippocampus (AAV5, AAV PHP.eB) or via systemic injection in the retro-orbital venous sinus (AAV PHP.eB). We collected new data on the transduction properties of locally injected PHP.eB and AAV5 viruses. A morphological examination and immunostainings of mouse brain slices revealed a dose-dependent shift of cellular tropism for locally injected PHP.eB from astroglial to astroglial-neuronal as the concentration increased. When the high doses of PHP.eB viruses were administered systemically, we observed strong astrocyte transduction throughout the brain, as confirmed by the morphological examination and GFAP immunostaining. AAV5 exhibited consistent astrocytic expression in all tested concentrations. The obtained results suggest that AAV5 is more suitable for astrocyte targeting in routine stereotaxic viral injection experiments. The widely used engineered PHP.eB capsid was originally designed for the transduction of both neurons and glia. Dual cellular tropism of PHP.eB viruses, observed using different doses and different delivery protocols (local vs. systemic), suggests that the usage of AAV5 is more reliable for astrocyte labeling and that intrahippocampal injection is more suitable than systemic injection for the preferential labeling of hippocampal astroglia.